Visual C# how to program - Deitel, Paul J.; Deitel, Harvey M., 1945- (Pearson Education Limited, 2018)
Created by world-renowned programming instructors Paul and Harvey Deitel, Visual C# How to Program, Sixth Edition introduces students to the world of desktop, mobile and web app development with Microsoft's® Visual C#® programming language. Students will use the .NET platform and the Visual Studio® Integrated Development Environment to write, test, and debug applications and run them on a wide variety of Windows® devices. At the heart of the book is the Deitel signature live-code approach - rather than using code snippets, the authors present concepts in the context of complete working programs followed by sample executions. Students begin by getting comfortable with the Visual Studio Community edition IDE and basic C# syntax. Next, they build their skills one step at a time, mastering control structures, classes, objects, methods, variables, arrays, and the core techniques of object-oriented programming. With this strong foundation in place, the authors introduce more sophisticated techniques, including searching, sorting, data structures, generics, and collections. Additional practice is provided through a broad range of example programs and exercises selected from computer science, business, education, social issues, personal utilities, sports, mathematics, puzzles, simulation, game playing, graphics, multimedia and many other areas